Functional exercise after total hip replacement (FEATHER) a randomised control trial. - Monaghan, Brenda (BMC Musculoskeletal Disorders 2012, 2012)
Background: Prolonged physical impairments in range of movement, postural stability and walking speed are commonly reported following total hip replacement (THR). It is unclear from the current body of evidence what kind of exercises should be performed to maximize patient function and quality of life. Methods/design: This will be a single blind multi centre randomized control trial with two arms. Seventy subjects post primary total hip arthroplasty will be randomized into either an experimental group (n=35), or to a control group (n=35). The experimental group will attend a functional exercise class twice weekly for a six week period from week 12 to week 18 post surgery. The functional exercise group will follow a circuit based functional exercise class supervised by a chartered Physiotherapist. The control group will receive usual care. The principal investigator (BM) will perform blinded outcome assessments on all patients using validated measures for pain, stiffness, and function using the Western Ontario and Mc Master Universities Osteoarthritis index (WOMAC). This is the primary outcome measurement tool. Secondary outcome measurements include Quality of life (SF-36), 6 min walk test, Visual Analogue Scale, and the Berg Balance score. The WOMAC score will be collated on day five post surgery and repeated at week twelve and week eighteen. All other measurements will be taken at week 12 and repeated at week eighteen. In addition a blinded radiologist will measure gluteus medius cross sectional area using real time ultrasound for all subjects at week 12 and at week 18 to determine if the functional exercise programme has any effect on muscle size. Discussion: This randomised controlled trial will add to the body of evidence on the relationship between muscle size, functional ability, balance, quality of life and time post surgery in patients following total hip arthroplasty. The CONSORT guidelines will be followed to throughout. Ethical approval has been gained from the Ethics committee Health Services Executive Dublin North East.
PUBLISHED
Keywords: Total hip replacement; Late stage exercise; Functional exercise; Physiotherapy; Mobility impairment